Penerapan Media Interaktif dan Metode untuk Meningkatkan Kualitas Pembelajaran Ilmu Sosial di SD Negeri 04 Palembang - Dea Utami; Yolanda, Yolanda; Sari Safitri; Frika Fatimah Zahra (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to explore and improve the quality of Social Studies (IPS) instruction at SD Negeri 04 Palembang by integrating interactive learning media and collaborative teaching strategies, especially in the “Map Layout” topic for fifth-grade students. Using a qualitative descriptive approach, the researchers gathered data through document analysis, conversations with teachers and students, as well as direct observation of learning activities. The findings show that the use of visual learning tools, cooperative group work, and contextual tasks related to students’ everyday environments helps make Social Studies lessons more engaging and meaningful. Simple interactive materials such as illustrated school layouts were shown to increase students’ participation and strengthen their understanding of spatial concepts. Overall, the integration of interactive media with collaborative learning approaches contributes to a more dynamic classroom atmosphere, supports deeper conceptual comprehension, and enhances students’ motivation to learn. This approach demonstrates strong potential for improving IPS learning outcomes in elementary education.